Analisis Makna Lam dalam Surat Al-Qalam - Khuzaima Mandhira Pusti; Kaila Salsabilla Renajaya; Fitria Nurrohmah; Syukronillah; Aang Saeful Milah (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
This research aims to describe the meaning of Lam in Surah Al-Qalam. The approach in this research is descriptive qualitative. Data were collected using note-taking techniques and went through the stages of data reduction, data display, conclusions, and verification. The results of this research show that there are 18 pieces of lam, which are divided into several parts, such as lam nahyi, lam harf nafyi, and lam taukid. Additionally, there is lam ghoiru amilah, comprising of 9 lams divided into five parts: lam zaidah, lam waqiah, lam muzhalaqah, lam ibtida', and lam fariqoh. The research also indicates that the function and meaning of the letter lam form a sentence that can only emerge after being combined with another sentence.